Implementation Of Bank Operational Risk Management In Human Resource Management At Bank Syariah Indonesia - Abib Novriyanto; Ashari Seribu Dinar; Eka Yuni Hartati; Febyviani Dwimutian; Ridwansyah Ridwansyah; Wan Ruslan Abdul Ghani; Mulya Jayanti Putri Septina (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
The operational risk management in Islamic banks is crucial to ensure the smooth functioning of the bank while adhering to Islamic principles. Operational risks in banks can arise from internal processes, human errors, system failures, and external events. These risks, when not managed effectively, can have significant impacts on the financial stability and reputation of the bank. The human factor (human resources) plays a pivotal role in operational risk, especially in banks following Sharia principles, where it is necessary to ensure that the employees are well-trained, competent, and have a strong understanding of Islamic financial laws. This paper discusses the role of human resource management in the operational risk management framework of Bank Syariah Indonesia (BSI). Effective human resource management ensures that the right employees are hired, trained, and retained, thus minimizing the potential risks caused by human errors. The focus of the paper is to assess how Bank Syariah Indonesia incorporates risk management strategies in their HR practices and explores the training and development programs aimed at enhancing employee competence in managing operational risks. The research highlights the importance of creating a risk-aware culture and building a strong risk management system within the bank, specifically focusing on improving the competencies of human resources to reduce operational risks.